THE CONTRIBUTION OF “CRITICAL GEOPOLITICS” IN THE UNDERSTANDING OF THE LEBANESE SOCIOPOLITICAL LABYRINTH - Cortes, Francisco Salvador Barroso (European Scientific Journal, ESJ, 2014)
Why is it important to study the distribution of power in Lebanon, whose theoretical framework is offered by ―Critical Geopolitics‖? In an attempt to answer this question we must analyze the distribution of settlements of different minorities, and communities, which will help us understand the impact they have on Lebanon, and the Geopolitical pressure that the war in Syria from the north side is presenting, and the pressure that could erupt again if a war between Hezbollah and Israel from the southern flank starts once again. This paper also provides a description and an explanation of the confessional community map of Lebanon. To do this, we will use the main ideological and cultural factors that affect the complex interplay of local and regional factors on Lebanese security and defense concerns. Using the theoretical framework of ―Critical Geopolitics‖ we will present the mosaic of communities that reflects the Geopolitical pressures experienced by this country from all its flanks and how domestic and foreign policies respond to this Geopolitical pressure.